My child has autism : the experiences of fathers and mothers in raising a child with autism in Singapore - Goh, Pei Xuan (2018)
A paucity of research examined the experience of parenting children with autism. Those which did focused almost exclusively on the experience of mothers while fathers were often underrepresented. In light of this, this study seeks to explore and examine the possible similarities and differences in the parenting experience of fathers and mothers. While similarities were found, I suggest that there are key differences in the experience of fathers and mothers. These differences can be attributed to the gender norms which continued to exert its influence on fathers’ and mothers’ perceptions about their roles and responsibilities in such situation. Similarities in experience are a result of new networks, connections and strategies that developed overtime as parents negotiate and come to terms with their child’s autism diagnosis. This research hopes to contribute to the existing research by considering how gender affects the experience of parenting a child with autism in Singapore.